Nano-Biosensors in Clinical Neuroscience: Opportunities, Challenges, and 2Translational Milestones - Suliyat Abiodun Aremu (My University, 2025)
The intersection of nanotechnology and neuroscience has catalyzed the development of nano-biosensors capable of real-time, high-resolution monitoring of brain activity. These nanoscale devices, utilizing materials such as graphene, nanowires, and flexible polymers, offer unprecedented potential for diagnosing and managing neurological disorders by enabling continuous neural recording with minimal invasiveness. This Perspective explores the clinical applications of nano-biosensors, including their use in epilepsy monitoring, Parkinson’s disease management, and brain-computer interfaces. We critically evaluate the opportunities nano-biosensors present for personalized medicine, closed-loop therapies, and minimally invasive diagnostics, alongside the significant challenges related to biocompatibility, device stability, data management, and ethical concerns. Finally, we highlight future directions for interdisciplinary collaboration and regulatory strategies necessary to safely and effectively translate nano-biosensors into clinical practice. While hurdles remain, nano-biosensors may herald a paradigm shift in the way we monitor, understand, and treat brain disorders.
Keywords: Nano-biosensors; Real-time neural monitoring; Clinical translation; Brain– 34computer interfaces; Closed-loop neurotherapeutics; Biocompatibility; Neural data ethics; Translational milestone